CHURCH AND AFRICAN DESCENT IN THE CORREGIMIENTO OF ARICA. MORE SHADOWS THAN LIGHTS IN THE PLAN OF GOD AND MEN. DOCuMENTARY RECORDS EIGHTEENTH CENTURY. - Briones Valentín, Viviana (Revista de Historia Social y de las Mentalidades, 2024)
The slave population or free afro descendant of Corregimiento of Arica was the subject of an evangelization, the same as in the rest of the Virreinato of Peru, according to the needs of the slave system. A church overcame for the economic expectations and exceeded by the demands of reproducing a christian moral of political and social effects failed or didn’t know how to materialize his evangelist vocation and Christian care required by this type of population. More shadows trying to portray this assistance or spiritual care that has say for the documents presented in this article corresponding to the 18th century, slaves or free afro descendant were asking to all lights